Analisis Harga Minyak Dunia, Nilai Tukar, dan Suku Bunga pada Tingkat Inflasi di Indonesia Periode 2015 - 2022 - Putri Setyawati; Milda Handayani; Bayu Seno Pitoyo; Tyna Yunita; Hasanuddin Hasanuddin (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The aim of this research is to determine the influence of World Oil Prices, Exchange Rates, and Interest Rates on the Inflation Rate in Indonesia for the 2015 – 2022 Period. The type of research is quantitative research. The sampling technique was total sampling, namely 96 data/samples with SPSS software version 26.0. Based on the research results, it shows that the world oil price and interest rate variable has a positive and significant effect on the inflation rate in Indonesia, but the exchange rate variable has no significant effect on the inflation rate in Indonesia. The research results also show that the variables of world oil prices, exchange rates, and interest rates simultaneously have a positive and significant effect on the inflation rate in Indonesia.